Ester Gendusa, Identità nere e cultura europea. La narrativa di Bernardine Evaristo (Altre Modernità, 2015)
Ester Gendusa, Identità nere e cultura europea. La narrativa di Bernardine Evaristo(Roma, Carocci, 2014, 239 pp., ISBN 9788843073795)di Paolo Caponi